An Analysis and Comparison of Commonly Available Prescribing Information Resources in North Indian Set Up - Neetu Sharma, Sandeep Batish, Anita Gupta (Journal of Applied Pharmaceutical Science)
To determine the prescribing information resources and the types of information about new drugs that Indian doctors perceived as important before prescribing and how they keep their information upto date . Also to determine if hospital doctors and General practitioners differed in their use of the sources. Two hundred general practitioners (GPs) and 200 hospital doctors were asked to rate information sources in terms of their importance for prescribing ‘old’ and ‘new’ drugs, and then to name the source from which information about the last new drug prescribed was actually derived. The study was carried out by information collection, by filling a questionnaire. Among 200 GPs, the Monthly Index of Medical Specialties (MIMS), pharmaceutical representatives and medical journal articles were most frequently rated as important for information on both old and new drugs . Among 200 hospital doctors, Refreshers courses by Govt.(Trainings),Monthly Index of Medical Specialties (MIMS) , and Hospital clinical meetings were of greatest importance. Information on the last new drug prescribed was derived from a broad range of sources. GPs and hospital doctors differ in their utilization of the prescribing information resources .This study generates the information that can be sought to help in shaping the development of health policy and the implementation of the Primary Health Care Strategy.
Keywords: prescribers, prescribing information, prescribing information resources, evidence based medicine, rational prescribing.